2010
DOI: 10.1016/j.yjmcc.2010.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the cardiac Na+–Ca2+ exchanger by sorcin via the interaction of the respective Ca2+-binding domains

Abstract: Sorcin is a penta-EF-hand protein that interacts with intracellular target proteins after Ca2+ binding. The sarcolemmal Na+/Ca2+ exchanger (NCX1) may be an important sorcin target in cardiac muscle. In this study, RNAi knockdown of sorcin, purified sorcin or sorcin variants was employed in parallel measurements of: (i) NCX activity in isolated rabbit cardiomyocytes using electrophysiological techniques and (ii) sorcin binding to the NCX1 calcium binding domains (CBD1 and (iii) using surface plasmon resonance a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 42 publications
1
35
0
Order By: Relevance
“…Sorcin is a calcium-binding protein, and the calcium-binding domain contains eight ␣-helices (A to H) organized in five calcium-binding motifs (EF1-EF5). EF2 and EF3 are linked by helix D and have a high affinity with metal (27). It has been previously reported that an F112L mutant of sorcin displays a marked decreased in Ca 2ϩ affinity (28).…”
Section: Resultsmentioning
confidence: 99%
“…Sorcin is a calcium-binding protein, and the calcium-binding domain contains eight ␣-helices (A to H) organized in five calcium-binding motifs (EF1-EF5). EF2 and EF3 are linked by helix D and have a high affinity with metal (27). It has been previously reported that an F112L mutant of sorcin displays a marked decreased in Ca 2ϩ affinity (28).…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, neuronal cells exposed to oxygen and glucose deprivation activate the Na þ /Ca 2þ exchanger NCX1, which is known to be a target protein of sorcin (14), and this is correlated with accumulation of Ca 2þ into the ER, and prevention of ER stress and apoptosis (42). Furthermore, increased levels of Ca 2þ in the ER have also been correlated with MDR phenotypes in cancer cells (41,43).…”
Section: Discussionmentioning
confidence: 99%
“…Sorcin is a Ca 2þ sensor which regulates the activity of the ryanodine receptor RyRs, the Na þ /Ca 2þ exchanger NCX, and the voltage-dependent L-type Ca 2þ channel (12)(13)(14) and that, by the interaction with these target proteins, is involved both in regulating Ca 2þ homeostasis and in modulating excitation-contraction coupling in the heart (15,16). Some evidence suggests involvement of sorcin in the drug resistance shown by human malignancies.…”
Section: Introductionmentioning
confidence: 99%
“…Calcium homeostasis Regulation of Ca 2+ channels, pumps, exchangers [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] Regulation of ER and cytosolic Ca 2+ concentration [4, Regulation of heart-muscle contraction [6][7][8][9][10][11][12][13][14][15][16][17][18]29,30] Cellular metabolism ER stress sensor, unfolded protein response regulation [20,22,[26][27][28]31] Regulation of mitosis, cytokinesis, cell cycle [17,22,26,27,32] Regulation of kinases [22,30,33,34] Regulation of glucose metabolism …”
Section: Events: Sorcin Role: References Relevant Studiesmentioning
confidence: 99%